Walk two moons - Creech, Sharon (New York : HarperCollins, 1994)
After her mother leaves home suddenly, thirteen-year-old Sal and her grandparents take a car trip retracing her mother's route. Along the way, Sal recounts the story of her friend Phoebe, whose mother also left.
Keywords: Death; Grandparents; Family life; Friendship